Protein supplementation does not augment adaptations to endurance exercise training - Jonvik, K. L.; Paulussen, K. J. M.; Danen, S. L.; Ceelen, I. J. M.; Horstman, A. M.; Wardenaar, F. C.; van Loon, L. J. C.; van Dijk, J. W. (Medicine & Science in Sports & Exercise, 2019)
Recently, it has been speculated that protein supplementation may further augment the adaptations to chronic endurance exercise training. We assessed the effect of protein supplementation during chronic endurance exercise training on whole-body oxidative capacity (V?O2max) and endurance exercise performance. Methods In this double-blind, randomized, parallel placebo-controlled trial, 60 recreationally active males (age, 27 ± 6 yr; body mass index, 23.8 ± 2.6 kg·m-2; V.O2max, 47 ± 6 mL·min-1·kg-1) were subjected to 12 wk of triweekly endurance exercise training. After each session and each night before sleep, participants ingested either a protein supplement (PRO; 28.7 g casein protein) or an isoenergetic carbohydrate placebo (PLA). Before and after the 12 wk of training, V?O2max and endurance exercise performance (~10-km time trial) were assessed on a cycle ergometer. Muscular endurance (total workload achieved during 30 reciprocal isokinetic contractions) was assessed by isokinetic dynamometry and body composition by dual-energy x-ray absorptiometry. Mixed-model ANOVA was applied to assess whether training adaptations differed between groups.